Tecnologia e cultura na obra Tina Respeito (2019) de Fefê Torquato - Souza, Luana Veneziano de (2023)
The present study seeks to reflect on the representations of technology and culture in the work Tina Respeito, by the Brazilian comic artist Fefê Torquato, released in 2019, by Mauricio de Sousa’s MSP label. In the analyses, the relations between the production contexts, the technical, social and symbolic materialities and the narratives that cross this graphic novel were considered. This artistic work is seen not only as a product, but as part of cultural practices that involve historically constituted values and behaviors. Based on the artist’s trajectory and the work processes that involve webcomics and the use of technology to create comics, we study the meanings constructed by the various elements of the language of comics: composition, layout of pages, scenarios, characterization of characters, effects of colors and graphics, gestures, speech, expressions, balloons, etc. The comic artist builds critiques of contemporary society, addressing different aspects of technology and culture, in addition to experimenting with many of her artistic strategies and the use of comic language to think about everyday life and build other worldviews.